Experimental Bariatric Surgery in Rats Generates a Cytotoxic Chemical Environment in the Gut Contents. - Li, Jia; Reshat, Reshat; Wu, Qianxin; Ashrafian, Hutan; Bueter, Marco; Le ROux, Carel; Darzi, Ara; Athanasiou, Thanos; Marchesi, Julian; Nicholson, Jeremy; Holmes, Elaine; Gooderham, Nigel (Frontiers in Microbiology, 2011)
Bariatric surgery, also known as metabolic surgery, is an effective treatment for morbid obesity which also offers pronounced metabolic effects including the resolution of type 2 diabetes and a decrease in cardiovascular disease and long-term cancer risk. However, the mechanisms of surgical weight loss and the long term consequences of bariatric surgery remain unclear. Bariatric surgery has been demonstrated to alter the composition of both the microbiome and the metabolic phenotype. We observed a marked shift towards Gammaproteobacteria, particularly Enterobacter hormaechei, following Roux-en-Y gastric bypass (RYGB) surgery in a rat model compared with sham operated controls. Fecal water from RYGB surgery rats was highly cytotoxic to rodent cells (mouse lymphoma cell line), although In contrast, fecal water from sham operated animals showed no/very low cytotoxicity. This shift in the gross structure of the microbiome correlated with greatly increased cytotoxicity in a regulatory acceptable mouse lymphoma assay. Urinary phenylacetylglycine and indoxyl sulfate and fecal GABA, putrescine, tyramine and uracil were found to be inversely correlated with cell survival rate. This profound co-dependent response of mammalian and microbial metabolism to RYGB surgery and the impact on the cytotoxicity of the gut luminal environment suggests that RYGB exerts local and global metabolic effects which may have an influence on long term cancer risk and cytotoxic load.